Replication data for The political consequences of housing (un)affordability - Cansunar, A; Ansell, B (University of Oxford, 2022)
Replication and data construction materials for Ansell and Cansunar 2021. Please note, users should apply to GESIS to download ISSP files. Data construction shows how to combine files.